2022
DOI: 10.1002/mrm.29484
|View full text |Cite
|
Sign up to set email alerts
|

Fast bound and pore water mapping of cortical bone with arbitrary slice oriented two‐dimensional ultra‐short echo time

Abstract: Purpose Extend fast, two‐dimensional (2D) methods of bound and pore water mapping in bone to arbitrary slice orientation. Methods To correct for slice profile artifacts caused by gradient errors of half pulse 2D ultra‐short echo time (UTE), we developed a library of predistorted gradient waveforms that can be used to interpolate optimized gradient waveforms for 2D UTE slice selection. We also developed a method to estimate and correct for a bulk phase difference between the two half pulse excitations used for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Notably, the required time for dual-echo UTE MRI sequence depends on the acquisition techniques. For example, two-dimensional (2D) UTE acquisition ( 32 , 33 ) is faster than a three-dimensional (3D) acquisition (using radial, spiral, or cones trajectories) ( 22 , 34 ), while among the 3D acquisitions, the spiral or Cones is faster than a radial technique. Moreover, the UTE scan time can be improved by several acceleration techniques such as the stretching spokes in Cones ( 35 ), compressed sensing ( 36 - 38 ), and parallel imaging ( 39 , 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the required time for dual-echo UTE MRI sequence depends on the acquisition techniques. For example, two-dimensional (2D) UTE acquisition ( 32 , 33 ) is faster than a three-dimensional (3D) acquisition (using radial, spiral, or cones trajectories) ( 22 , 34 ), while among the 3D acquisitions, the spiral or Cones is faster than a radial technique. Moreover, the UTE scan time can be improved by several acceleration techniques such as the stretching spokes in Cones ( 35 ), compressed sensing ( 36 - 38 ), and parallel imaging ( 39 , 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cortical bone tissue with a fast decay signal 22 is an ideal organism matter for testing the short-T 2 imaging capacity of the KSSI sequence. 1 H imaging of swine rib bone confirmed that the TE can be shortened to the hardware performance limitation and demonstrated the feasibility of KSSI 1 H imaging for short-T 2 material or biological tissue.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The signal ratio calculation in dual-echo UTE imaging ( 20 ) and the signal ratio between UTE and inversion recovery UTE (IR-UTE) ( 21 ) are two remarkable examples of rapid UTE-based bone evaluation techniques, each of which takes less than 5 minutes. Notably, the required time for such measurements depends on the UTE acquisition techniques, which can be two-dimensional (2D) (using cartesian or radial trajectories) ( 22 , 23 ) or three-dimensional (3D) (using cartesian, radial, spiral, or cones trajectories) ( 10 ). Generally, a 2D UTE sequence is faster than a 3D UTE sequence, and a spiral acquisition is faster than a radial or cartesian acquisition.…”
Section: Introductionmentioning
confidence: 99%